Production of pellets for combustion and physisorption of CO2 from hydrothermal carbonization of food waste – Part I: High-performance solid biofuels - Moreira, Bruno Rafael de Almeida [UNESP]; Cruz, Victor Hugo [UNESP]; Pérez, Juan Fernando; Viana, Ronaldo da Silva [UNESP] (Elsevier, 2021)
Our study analyzed if it could be possible for converting hydrochar from food waste and its ash into solid biofuels and adsorbents of CO2. The pilot-scale manufacturing of pellets consisted of carbonizing food waste at 200.00 °C and 1.50 MPa for 1.00–2.00 h then pressing its hydrochar and ash with spent coffee ground on an automatic pelletizer at 75.00–100.00 MPa and 150.00 °C for 90.00 s. Products with co-addition were highly durable (97.95–98.05%), burned themselves out stably with 2.75–3.25 W g−1 heat flow and tended to have low slagging, despite their significant amount of ash of 2.80–2.90%. Hypothetically, they replaced approximately 10.00% of generation of electricity and saved 112.20 × 106 Mg yr−1 emission of CO2 from coal. Our insights are timely and absolutely will assist with tackling social and environmental impacts of generation of hazardous (bio)waste and emission of CO2 from coal-like fossil fuels.
Keywords: Additive; Adsorbent; Ash; Hydrochar; Municipal solid waste; Spent coffee ground